2017
DOI: 10.1080/2162402x.2017.1407898
|View full text |Cite
|
Sign up to set email alerts
|

Development of chimeric antigen receptors targeting T-cell malignancies using two structurally different anti-CD5 antigen binding domains in NK and CRISPR-edited T cell lines

Abstract: Relapsed T-cell malignancies have poor outcomes when treated with chemotherapy, but survival after allogeneic bone marrow transplantation (BMT) approaches 50%. A limitation to BMT is the difficulty of achieving remission prior to transplant. Chimeric antigen receptor (CAR) T-cell therapy has shown successes in B-cell malignancies. This approach is difficult to adapt for the treatment of T-cell disease due to lack of a T-lymphoblast specific antigen and the fratricide of CAR T cells that occurs with T-cell anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
66
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 69 publications
(92 reference statements)
0
66
1
Order By: Relevance
“…Approaches directed against this antigen face the same difficulties as CD7-directed approaches since CD5 is also a pan T-cell marker. Two studies showed that NK-92 expressing CD5-directed CARs were efficient in vitro against CD5-positive cell lines and primary tumour cells, and developed anti-tumour activity in vivo [33, 34]. Additionally, the use of anti-CD3 CAR-equipped NK-92 against primary peripheral T-cell lymphoma cells and T-cell leukaemia cell lines was investigated showing cytotoxic activity in vitro and against Jurkat cells in a xenogeneic mouse model [35].…”
Section: Car-modified Nk Cells Against Leukaemia and Lymphomamentioning
confidence: 99%
“…Approaches directed against this antigen face the same difficulties as CD7-directed approaches since CD5 is also a pan T-cell marker. Two studies showed that NK-92 expressing CD5-directed CARs were efficient in vitro against CD5-positive cell lines and primary tumour cells, and developed anti-tumour activity in vivo [33, 34]. Additionally, the use of anti-CD3 CAR-equipped NK-92 against primary peripheral T-cell lymphoma cells and T-cell leukaemia cell lines was investigated showing cytotoxic activity in vitro and against Jurkat cells in a xenogeneic mouse model [35].…”
Section: Car-modified Nk Cells Against Leukaemia and Lymphomamentioning
confidence: 99%
“…Various approaches have been used to overcome these challenges, including CRISPR-Cas9 genome editing to remove the antigen from the CAR T cells [45][46][47], Tet-OFF expression system to limit fratricide during ex vivo expansion [48], protein expression blocker (PEBL) to retain the antigen in the ER/Golgi to prevent cell surface expression [49,50], or using CAR-modified natural killer cells instead of T cells [47,[51][52][53][54]. Additionally, to date, four targets have been investigated as targets for CAR T cell therapy for the treatment of T cell malignancies with limited to no expression in the normal population of T cells, CD30, CD37, TRBC1, and CD1a [55][56][57][58].…”
Section: Translating Car T Cell Therapy For Treatment Of T Cell Maligmentioning
confidence: 99%
“…As a result, fratricide was observed only transiently, allowing the CD5-CAR T cells to expand. These cells had significant Genome editing of target antigen [45][46][47] Targeting antigens with limited expression on T cells (e.g., CD30, CD37, TRBC1, CD1a) [55][56][57][58] Tet-OFF expression system [48] Protein expression blockers (PEBLs) [49] Using NK cells or NK-92 cells [47,[51][52][53][54]60] T cell aplasia Targeting antigens with limited expression on T cells (e.g., CD30, CD37, TRBC1, CD1a) [55][56][57][58] mRNA electroporation…”
Section: Cd5mentioning
confidence: 99%
See 1 more Smart Citation
“…Allogeneic CD7 directed CAR‐T that have been modified by CRISPR/Cas9 to not express CD7 are in development for T‐cell malignancies . In addition, CAR‐T directed at CD2, CD5, and CD38 are under development for T‐cell cancers, including T‐ALL . CD123 and CD33 directed CAR‐T approaches are being explored in acute myelogenous leukemia (AML) .…”
Section: Efficacy Of Car‐t In Hematologic Malignanciesmentioning
confidence: 99%